PENINGKATAN KINERJA RANTAI PASOK BAWANG MERAH (STUDI KASUS: KABUPATEN BREBES) - Lely Rachma Septiana, Machfud, dan Indah Yuliasih (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Shallots supply chain faces many problems and challenges, so need efforts to improve the performance. This study was conducted to: 1) analyze conditions of the shallots supply chain using the framework discussion of FSCN (Food Supply Chain Network), 2) measure performance of the shallots supply chain using the rating scale method and indicator assessment adapted from the SCOR (Supply Chain Operations Reference) model, and 3) formulate efforts to improve performance of shallots supply chain by conducting gap analysis and problem analysis. The study was conducted in Brebes as the largest shallots production center in Indonesia. The results showed that the members of shallots supply chain are farmers, traders, wholesalers, and retailers or traditional local market traders. The performance measurement to shallots supply chain in Brebes showed the value of 3.57 during the season and 3.28 in off season. Efforts to improve the supply chain performance of shallots in Brebes include building proper inventory system; build partnerships, coordination and collaboration among the members of the chain and institutional capacity building of farmers, address the low availability of shallots especially during the off season; increase the availability of market information; and solve the problems concerning the distribution mechanism.Keywords: shallots, supply chain, performance measurement,performance improvement